2016
DOI: 10.1093/mnras/stw023
|View full text |Cite
|
Sign up to set email alerts
|

The OGLE-III planet detection efficiency from six years of microlensing observations (2003–2008)

Abstract: We use six years (2003)(2004)(2005)(2006)(2007)(2008) of OGLE-III microlensing observations to derive the survey detection efficiency for a range of planetary masses and projected distances from the host star. We perform an independent analysis of the microlensing light curves to extract the event parameters and compute the planet detection probability given the data. 2433 light curves satisfy our quality selection criteria and are retained for further processing. The aggregate of the detection probabilities o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Integration was done in each bin separately, assuming one companion for each star with given properties. Tsapras et al (2016) showed their results in physical projected separation and companion mass, which we translated back to (s, q) assuming r E = 2.3 AU and M l = 0.4 M . In Table 4 we present how many objects each of OGLE-2011-BLG-0173 analysis 23 these surveys would detect under our assumptions and how many were in fact detected.…”
Section: Ice Giant Occurrence Ratesmentioning
confidence: 90%
See 2 more Smart Citations
“…Integration was done in each bin separately, assuming one companion for each star with given properties. Tsapras et al (2016) showed their results in physical projected separation and companion mass, which we translated back to (s, q) assuming r E = 2.3 AU and M l = 0.4 M . In Table 4 we present how many objects each of OGLE-2011-BLG-0173 analysis 23 these surveys would detect under our assumptions and how many were in fact detected.…”
Section: Ice Giant Occurrence Ratesmentioning
confidence: 90%
“…There are just a few detections of objects in the considered separation range, which prevent us from drawing definitive conclusions. We note that there are many events that were searched for distant companions, which resulted in only four detections altogether: on order of 20, 000 events alerted by the OGLE and MOA surveys, in addition to the Tsapras et al (2016) and Suzuki et al (2016) samples. The numbers presented in Table 4 suggest that companions in the lowest mass ratio range are common (see also Foreman-Mackey et al 2016).…”
Section: Ice Giant Occurrence Ratesmentioning
confidence: 91%
See 1 more Smart Citation
“…These 200−600 events include 5−10% anomalous events deviating from a simple static point lens and are reported by anomaly detectors. Examples of different anomaly types can be found in Tsapras et al (2016). Not all anomalous events can be monitored continuously, and even with two-to-three follow-up telescopes per site we can only cover a handful of events with high enough cadence.…”
Section: Priority and Planet Detection Zonesmentioning
confidence: 99%
“…The presence of these unseen planets is then revealed through the detection of brief but intense changes in the measured brightness. This method opens up a unique window to the population of low-mass exoplanets at or beyond the snow-line, which is unavailable to other detection methods (Tsapras et al 2016;Cassan et al 2012;Gould et al 2010).…”
Section: Introductionmentioning
confidence: 99%